Factors affecting the management of residential building construction projects of entrepreneurs. Under the epidemic situation of the Coronavirus 2019 in Minburi District, Bangkok - ทะชัยวงษ์ นที; Kongsong, Asst.Prof.Waranon; Snongtaweeporn, Dr.Teeradej; Thammapornram, Dr.Chaleeporn (Journal of Dhamma for Life, 2023)
The purposes of this research were: 1) to explore factors affecting the management of residential building construction projects of entrepreneurs, and 2) to study the impacts on entrepreneurs in the management of residential building construction projects under the epidemic situation of the Coronavirus 2019 in Minburi District, Bangkok. This research is a quantitative research. The samples were 287 employees of residential building construction companies in Minburi District, Bangkok. The research questionnaire was used as a tool to collect data. Data were analyzed by descriptive analysis and hypotheses were tested by Pearson Correlation Coefficient. The findings revealed that: 1) the factors affecting the management of residential building construction projects of entrepreneurs were at a high level with mean values of 3.83 and S.D. of 0.65. In particular, the compliance with government orders and announcements had mean values of 4.27 and S.D. of 0.85, followed by personnel with mean values of 4.00 and S.D. of 0.72, construction management with mean values of 3.77 and S.D. of 0.69, and material equipment or machinery with mean value of 3.27 and S.D. of 0.72 respectively. 2) The impacts on entrepreneurs in the management of residential building construction projects under the epidemic situation of the Coronavirus 2019 in Minburi District, Bangkok were at a moderate level with mean values of 3.00 and S.D. of 0.85.